Pengaruh Komisaris Independen, Profitabilitas dan Transfer Pricing Terhadap Tax Avoidance Pada Perusahaan Sektor Barang Baku - Dwityas, Fitria Sekar; Hernat, Okevanrianus Putra (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2025)
The purpose of this study is to examine the influence of independent commissioners, profitability, and transfer pricing on tax avoidance in companies within the raw materials sector. This quantitative research utilizes secondary data, specifically annual financial reports obtained from the official website of the Indonesia Stock Exchange. The population consists of all companies in the raw materials sector listed on the Indonesia Stock Exchange from 2020 to 2024. Using purposive sampling, 20 companies meeting the sample criteria were selected. Data analysis was conducted using multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS) version 26. The results indicate that independent commissioners have a t-statistic significance value of 0.045, which is less than 0.05, with a positive β1 coefficient of 0.166. This suggests that a higher proportion of independent commissioners is associated with a higher Effective Tax Rate (ETR), indicating lower tax avoidance. Profitability has a t-statistic significance value of 0.000, less than 0.05, with a negative β2 coefficient of 0.864, implying that higher profitability leads to a lower ETR and thus higher tax avoidance. Transfer pricing shows a t-statistic significance value of 0.057, greater than 0.05. Partially, independent commissioners have a negative effect on tax avoidance, profitability has a positive effect, and transfer pricing has no effect. Simultaneously, the variables of independent commissioners, profitability, and transfer pricing significantly influence tax avoidance.